TAHSIN JAWDAT TA’LIM AL-LUGHAH AL-‘ARABIYAH MIN KHILAL TATHBIQ AL-MANHAJ AL-DIRASI AL-MUSTAQILL: تحسين جودة تعليم اللغة العربية من خلال تطبيق المنهج الدراسي المستقل - Ahmad Taqiyudin; Kamal Yusuf (Tarbiyah Faculty of Ibrahimy University Ibrahimy University, Situbondo, Indonesia, 2025)
The advancement of educational quality in Indonesia has been marked by the implementation of various curricula, including the Independent Study Curriculum, which grants greater flexibility in the selection of learning strategies and materials, particularly in Arabic language instruction. This study aims to investigate the enhancement of Arabic language learning quality at Bina Insani Islamic Junior High School Surabaya, through the application of the Independent Study Curriculum. The method employed is qualitative research design with a case study approach, data were gathered via classroom observations, teacher interviews, and analysis of student performance evaluations. Among the various pedagogical models integrated into the curriculum, project based learning has emerged as a prominent instructional strategy applied by Arabic teachers. The findings reveal that this approach significantly increases student engagement, fosters contextual and meaningful language comprehension, and enables teachers to adapt instruction to students' diverse linguistic backgrounds and learning levels. Furthermore, the implementation of the Independent Study Curriculum contributes to consistent and equitable academic performance across student groups. This research provides practical implications for Arabic language educators seeking to apply flexible and differentiated models under national curriculum frameworks, while also contributing to scholarly discourse on curriculum innovation and contextualized language pedagogy.